Immobilization of alpha-amylase onto cyclic carbonate bearing hybrid material - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCI LTD, 2009)
Under ambient conditions, 4-((3-trimethoxysilyl)propoxy)methyl)1,3-dioxolan-2-one was synthesized from 3-glycidyloxypropyl trimethoxysilane. Methacrylate and cyclic carbonate functional hybrid matrix was prepared by sol-gel method. alpha-Amylase was covalently bounded onto the matrix via cyclic carbonate functionality. Immobilization yield was found as 34.4 +/- 2.6 mg per gram of hybrid matrix. The maximum activity was observed at pH 6.5. Immobilization did not change the pH-dependency of the enzyme. The immobilized enzyme had a higher activity at elevated temperature (50-80 degrees C) than the free one. Immobilized enzyme exhibited 80% activity after 20 runs and 69% after 30 runs. Free enzyme lost its activity completely within 15 days. Immobilized enzyme lost only 30% of its activity in 25 days. V-max values for the free and immobilized enzymes were calculated as 58 x 10(-3) and 5.2 x 10(-3) mg/ml min(-1), respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amylase; Enzyme immobilization; Cyclic carbonate; Sol gel; UV curing; COVALENT IMMOBILIZATION; ALKALINE-PHOSPHATASE; VINYLENE CARBONATE; ENZYME-ACTIVITY; STABILITY; HYDROLYSIS; BEADS; IMPROVEMENT; CARRIERS; RESIN